Caracterização de ligantes e misturas asfálticas modificados com a adição de Trinidad Lake Asphalt - Fengler, Ricardo Zardin (2018)
The use of modifiers to improve the performance of asphalt materials when subjected to loading and climate effects has become an increasingly common practice in Brazil. Among the modifiers, the natural asphalt Trinidad Lake Asphalt (TLA) has characteristics that compensate some deficiencies of conventional petroleum-based asphalt binders, increasing the service life and improving the pavement performance. This study evaluated the influence of the addition of different TLA contents (15%, 25% and 50%) on the properties of two Brazilian petroleum-based asphalt binders of conventional use (AC 30/45 and AC 50/70) and the performance of asphalt mixtures. The properties of the asphalt binders were obtained through tests that are included in the Brazilian specification and a Dynamic Shear Rheometer was used to determine their rheological characteristics. Mechanical tests were performed to characterize the stiffness, resistance to permanent deformation and fatigue damage, and susceptibility to induced moisture damage of asphalt mixtures. The results obtained in this research indicate that the addition of TLA stiffens the asphalt binders (and consequently the asphalt mixture) and improves its rutting resistance. The fatigue damage resistance of the materials was not necessarily affected by the stiffening effect provided by the TLA, especially if a proper amount is added to the conventional petroleum-based binder.